The Craft of Basket Making in the Lubny Area: Traditions and Contemporary Situation - Verhovska, Maria (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2023)
Locally made baskets from bulrushes have long been used village women in the Lubny area (Poltava oblast) for carrying milk and vegetables to town for the market. People also used them to take food and water for themselves to the fields where they worked. The zemstvo (local landholders’ administration) supported the development of artisanal crafts at the end of the 19th century. Substantial changes occurred in artisanal crafts with the arrival of Soviet rule. People were required to join аn organized work brigade to continue such trades. Based on fieldwork, I provide a description of the artisanal craft in the first half of the 20th century and as it changed since that time. Gradually, with the development of industry, the need for baskets of this type decreased, and the craft began to decline. The generation that learned to make baskets in the 1950s and 1960s is now passing away.